Kinematic Strategies for Walking Across a Destabilizing Rock Surface() - Gates, Deanna H. (2011)
It is important to understand how people adapt their gait when walking in real-world conditions with variable surface characteristics. This study quantified lower-extremity joint kinematics, estimated whole body center of mass height (COM(VT)), and minimum toe clearance (MTC) while fifteen healthy, young subjects walked on level ground (LG) and a destabilizing loose rock surface (RS) at four controlled speeds. There were no significant differences in average step parameters (length, time, or width) between the walking surfaces. However, the variability of these parameters increased twofold on the RS compared to LG. When walking on the RS, subjects contacted the surface with a flatter foot and increased knee and hip flexion, which enabled them to lower COM(VT). Subjects exhibited increased hip and knee flexion and ankle dorsiflexion during swing on the RS. These changes contributed to a 3.8 times greater MTC on the RS compared to LG. Peak hip and knee flexion during early stance and swing increased with walking speed, contributing to decreased COM(VT) and increased MTC. Overall, subjects systematically adapted their movement kinematics to overcome the challenge imposed by the destabilizing loose rock surface.